(untitled) (Research, Society and Development, 2025)
Introduction: Proton magnetic resonance spectroscopy (¹H-MRS) is a noninvasive tool of great relevance for detecting metabolites in brain tumors, allowing the early identification of biochemical alterations before morphological changes appear in conventional imaging. However, technical factors such as magnetic field strength and differences between equipment manufacturers may affect diagnostic accuracy. Objectives: To analyze the main metabolic findings obtained through ¹H-MRS in brain tumors and to compare the performance of different manufacturers (Siemens, GE, and Philips) operating at 1.5T and 3T magnetic fields, focusing on diagnostic sensitivity. Method: A systematic review was conducted according to PRISMA guidelines. Studies published in the last ten years in MEDLINE/PubMed databases that applied ¹H-MRS for brain tumor assessment were included, focusing on the detection of metabolites such as N-acetyl aspartate (NAA), choline (Cho), creatine (Cr), lactate (Lac), and myo-inositol (Mi). A total of 33 articles met the eligibility criteria. Results: Magnetic field strength had a greater impact on spectral quality than manufacturer differences. 3T systems demonstrated superior spectral resolution, higher signal-to-noise ratio, and greater ability to detect low-concentration metabolites such as Mi and Lac. Metabolic ratios (NAA/Cr and Cho/Cr) were more accurate at 3T. Variations among Siemens, GE, and Philips systems were minimal and clinically insignificant. Conclusion: ¹H-MRS is a valuable technique for metabolic evaluation, aiding in the diagnosis and monitoring of brain tumors. Higher magnetic fields (3T) provide improved sensitivity and specificity, and protocol standardization is essential for multicenter studies.